1960
DOI: 10.1111/j.2042-7158.1960.tb10454.x
|View full text |Cite
|
Sign up to set email alerts
|

Vegetable Purgatives Containing Anthracene Derivatives: Part XI. Further Work on the Aloin-like Substance ofRhamnus purshiana DC

Abstract: The aloin‐like substance formerly referred to as Compound A1, has been resolved into four closely allied anthraquinone derivatives by paper chromatographic and countercurrent techniques. Two of these substances have been isolated in pure form and their general properties, melting point, optical rotation, RF values and ultra‐violet light absorption curves are recorded. Treatment with ferric chloride yields aloe‐emodin from both, and each on mild hydrolysis, produces barbaloin. The names Cascaroside A and Cascar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1963
1963
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Preliminary studies on the dried bark of this species enabled the identification of anthraquinone derivatives as its major compounds (Curica et al, 2008). Moreover, literature reviews showed that the pharmacological properties of F. alnus and F. purshiana are mainly due to the presence of this class of compounds (Fairbairn & Mital, 1958; Fairbairn & Simic, 1960; Cresseri et al, 1966; WHO, 2004 a , 2004 b ).…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies on the dried bark of this species enabled the identification of anthraquinone derivatives as its major compounds (Curica et al, 2008). Moreover, literature reviews showed that the pharmacological properties of F. alnus and F. purshiana are mainly due to the presence of this class of compounds (Fairbairn & Mital, 1958; Fairbairn & Simic, 1960; Cresseri et al, 1966; WHO, 2004 a , 2004 b ).…”
Section: Introductionmentioning
confidence: 99%
“…Chrysophanol anthrone C-glycoside (Chrysaloin) ( Fig. 3C) has been reported from cascara extracts (Fairbairn & Simic, 1960), but has not as yet been described from Aloe exudates.…”
mentioning
confidence: 97%
“…Barbaloin has also been found in extracts from cascara bark (Rhamnus purshiana DC.) (Fairbairn & Simic, 1960). Following the resolution of A and B stereoisomeric cascarosides it was suggested that barbaloin might be similarly resolved into two diastereomers (Fairbairn, 1964) and this was achieved by HPLC, yielding two substances differing in the configuration of the glucose residue at the C , , carbon atom (Auterhoff, Graff, Eurisch & Alexa, 1980; Grun & Franz, 1979).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…BARBALOIN, 10( 1)-deoxyglucosyl aloe-emodin anthrone, is an important constituent of aloes and has recently been shown to occur in cascara (Rhamnus purshiuna D.C. bark) in the form of glycosides (Fairbairn and Simic, 1960). A method of determining the barbaloin content of these crude drugs would therefore be useful in their evaluation.…”
mentioning
confidence: 99%